2007
DOI: 10.2165/00003495-200767150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Modern Management of Small-Cell Lung Cancer

Abstract: In this article, we review best standard practice for the management of small-cell lung cancer (SCLC) and indicate the likely areas of development over the next 5-10 years. A number of prognostic scores have been developed and these allow more rational decisions on treatment. Treatment with cisplatin plus etoposide with early, concurrent radiotherapy is the standard of care for patients with limited-stage disease (LD) suitable for this approach. A 5-year survival rate of 25% has been reported for concurrent hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…A more detailed analysis identified CpG sites 4,6,7,8,11,17,20, and 21 as sites demethylated in both A540 and H157 within 48 hours of 5-aza-dC treatment. Sites that become methylated with NNK treatment seem to differ with dose and the duration of treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A more detailed analysis identified CpG sites 4,6,7,8,11,17,20, and 21 as sites demethylated in both A540 and H157 within 48 hours of 5-aza-dC treatment. Sites that become methylated with NNK treatment seem to differ with dose and the duration of treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Standard first line treatment for small-cell lung cancer (SCLC) includes platinum-based chemotherapy, generally with the DNA and protein cross-linking agent cis-platinum-(II)-diamine dichloride (cisplatin) or carboplatin plus etoposide, a topoisomerase II inhibitor, with or without radiation (3)(4)(5)(6). Treatment of non-small cell lung carcinoma may include surgical resection, radiotherapy, and/or platinum-based chemotherapy (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…It is generally accepted that the life expectancy of SCLC patients depends on the extent of disease and the response to chemotherapy. Performance status (PS), gender, disease extent and response to chemotherapy have been evaluated as prognostic factors (1). Foster et al revealed that the number of metastatic sites was also a prognostic factor in ED-SCLC patients, regardless of the location of the metastatic site (2).…”
Section: Introductionmentioning
confidence: 99%
“…During and after chemotherapy, cancer cells often become resistant to multiple drugs, which affects the effectiveness of chemotherapy and leads to increased mortality (11,36). The H446/DDP cell line was derived from H446 cells that were made resistant to cisplatin, which is in a category of drugs commonly used in clinical chemotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, an effective way to treat SCLC multi-drug resistance has been reported (11). NHE-1 can directly interact with other regulatory cellular signaling pathways and is a multifaceted regulator of cell migration, proliferation, and cell death (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%